Ultraviolet crosslinking high-transparency polyvinyl chloride cable material and preparation method thereof

Through modified catalyst and ultraviolet cross-linking technology, the problem of deHCL reaction of PVC cable materials during ultraviolet radiation is solved, and the rapid cross-linking and performance improvement of the material is achieved.

CN119410082APending Publication Date: 2025-02-11SHANGHAI NEW SHANGHUA POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411540416.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

PVC cable materials are prone to deHCL reactions when irradiated with ultraviolet light, resulting in poor performance.

Method used

The modified catalyst is used to coat the rare earth catalyst with EVA solution, combined with ultraviolet crosslinking technology, and inhibit the chain reaction of macromolecular chain deHCL to promote rapid crosslinking of materials.

Benefits of technology

It significantly improves the heat resistance and mechanical properties of cable materials, reduces the loss of rare earth catalysts, and achieves high transparency and excellent electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112666540000071
    Figure BDA0005112666540000071
  • Figure BDA0005112666540000081
    Figure BDA0005112666540000081
Patent Text Reader

Abstract

The invention relates to the technical field of PVC (polyvinyl chloride) cable materials, and particularly discloses an ultraviolet crosslinking high-transparency polyvinyl chloride cable material and a preparation method thereof. The ultraviolet crosslinking high-transparency polyvinyl chloride cable material is prepared from the following components in parts by weight: 100 parts of polyvinyl chloride resin, 25 to 31 parts of a plasticizer, 1.4 to 2.0 parts of a crosslinking agent, 1.3 to 2.0 parts of a photoinitiator, 1.5 to 1.6 parts of a stabilizer, 0.2 to 0.3 part of an antioxidant, 1.0 to 1.2 parts of a lubricant and 6.3 to 12 parts of a modified catalyst, the modified catalyst is obtained by coating a rare earth catalyst with an EVA solution as a wall material. According to the ultraviolet crosslinking high-transparency polyvinyl chloride cable material disclosed by the invention, the contained rare earth ions inhibit a chain reaction of removing HCL from a macromolecular chain; and the EVA resin is used for coating, so that the activity of the rare earth is protected to play a role in the ultraviolet crosslinking process, and the ultraviolet crosslinking cable material with excellent performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PVC cable materials, and more specifically, to an ultraviolet light cross-linked high-transparency polyvinyl chloride cable material and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) cable materials have excellent properties such as good electrical insulation, heat resistance, chemical resistance, mechanical strength and fire resistance. They are widely used in electricity, communications, construction and other fields, and have great application prospects in the cable industry.

[0003] The changes in the internal structure of the PVC system caused by cross-linking make the cable material not only able to withstand work in high temperature environments, but also have good electrical insulation properties and chemical corrosion resistance. At present, the main cross-linking methods include radiation cross-linking, chemical cross-linking, blending cross-linking, modified cross-linking and UV cross-linking. Among them, UV cross-linking has attracted much attention due to its ease of use and high efficiency.

[0004] However, when PVC molecules are irradiated with ultraviolet light, it is difficult to obtain materials with better performance due to the HCL removal reaction. Summary of the invention

[0005] In order to suppress the HCL removal reaction of PVC cable materials when irradiated with ultraviolet light, the present application provides a UV-crosslinked high-transparency polyvinyl chloride cable material and a preparation method thereof.

[0006] In the first aspect, the present application provides a UV-crosslinked highly transparent polyvinyl chloride cable material, which adopts the following technical solution: A UV-crosslinked high-transparency polyvinyl chloride cable material comprises the following components in parts by weight: 100 parts of polyvinyl chloride resin, 25-31 parts of plasticizer, 1.4-2.0 parts of crosslinking agent, 1.3-2.0 parts of photoinitiator, 1.5-1.6 parts of stabilizer, 0.2-0.3 parts of antioxidant, 1.0-1.2 parts of lubricant and 6.3-12 parts of modified catalyst; The modified catalyst is obtained by using EVA solution as the wall material and coating the rare earth catalyst.

[0007] By adopting the above technical solution: introducing rare earth catalysts, the interaction between rare earth ions and different groups such as carboxyl and polyolefins integrates polymer materials, thereby improving the heat resistance of the materials and inhibiting the chain reaction of macromolecular chains to remove HCL, so that the cable materials can be quickly cross-linked under ultraviolet light. Coating with EVA solution, on the one hand, with the help of the good light transmittance of EVA resin, it is easy to penetrate light and is conducive to the ultraviolet light cross-linking of polyvinyl chloride; on the other hand, it has good tolerance and cross-linkability, forming a coating layer on the surface of the rare earth catalyst, so that the rare earth catalyst is not only highly active, but also will not be consumed in the processing of cable materials, so that it can play a better role in the ultraviolet light irradiation process.

[0008] Optionally, the EVA solution is a mixed solution of EVA resin and ethylene glycol ethyl ether acetate, and the vinyl acetate content of the EVA resin is ≥30%.

[0009] By adopting the above technical solution: EVA resin with vinyl acetate content ≥30% has more functional groups and greater polarity, which is conducive to cross-linking and better fluidity, thus facilitating dispersion, so as to better form a protective film on the surface of the rare earth catalyst to protect the rare earth activity.

[0010] Ethylene glycol ether acetate solution has a very strong dissolving ability and can dissolve EVA at room temperature. During the hydrolysis of EVA, the -CO- bond of the carboxylic acid will be partially broken, the free H will form a hydroxyl group, and the carbonyl group in ethylene glycol ether acetate will also be broken to obtain a uniform sol.

[0011] Optionally, the weight ratio of the EVA resin to ethylene glycol ethyl ether acetate is (0.5-1):1.

[0012] By adopting the above technical solution: when the EVA concentration is within the above range, the coating effect on the rare earth catalyst is better, and the rare earth catalyst is fully coated and plays a role.

[0013] Optionally, the weight ratio of the rare earth catalyst to the EVA resin is 1:(5-10).

[0014] By adopting the above technical solution: when the addition amount of the rare earth catalyst is within the above range, the prepared modified catalyst significantly improves the performance of the cable material.

[0015] Optionally, the rare earth catalyst is one or more of neodymium chloride, neodymium oxide, praseodymium oxide, lanthanum oxide, cerium oxide, and samarium oxide.

[0016] By adopting the above technical solution, all the above rare earth catalysts can be used, and the properties of the prepared cable materials are better.

[0017] Optionally, the degree of polymerization of the polyvinyl chloride resin is 1000-2500.

[0018] By adopting the above technical solution: polyvinyl chloride resins with a degree of polymerization in the range of 1000-2500 can be used, but after testing, when polyvinyl chloride resins with a degree of polymerization in the range of 1800-2500 are used, the mechanical properties of the cable material are better and meet higher requirements.

[0019] Optionally, the plasticizer is one or more of dibutyl phthalate, dioctyl phthalate, trioctyl trimellitate, dioctyl terephthalate, diisononyl cyclohexane-1-,2-dicarboxylate, polyester plasticizer, epoxy soybean oil, dioctyl sebacate, and dioctyl adipate.

[0020] By adopting the above technical solution, all the above plasticizers can be used, and the properties of the prepared cable material are better.

[0021] Optionally, the cross-linking agent is: one or more of: 1,1-bis(tert-butylperoxide)-3,3,5-trimethylcyclohexane, trithiocyanuric acid, triallyl isocyanurate, zinc acetylacetonate, diisopropyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, diethylenetriamine, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-isopropylimidazole, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, triethylenetetramine, dimethylaminopropylamine, and vinyltriethoxysilane.

[0022] By adopting the above technical solution, all the above cross-linking agents can be used, and the properties of the prepared cable material are better.

[0023] Optionally, the photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-methyl-1- (4-methylthiophenyl) -2-morpholinyl-1-propanone, 2-dimethylamino-2- (4-methyl) benzyl-1- [4- (4-morpholinyl) phenyl] -1-butanone, benzoin dimethyl ether, benzoin ethyl ether, benzoin butyl ether, diphenyl acetophenone, α, α-dimethoxy-α-phenyl acetophenone, One or more of α,α-diethoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone, bisbenzoylphenylphosphine oxide, benzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0024] The antioxidant is one or more of 2,4-dimethyl-6-(1-methylpentadecyl)-phenol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-di-tert-butyl-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, dimethylbenzene dibutylbenzofuranone, and N-phenyl-2-naphthylamine.

[0025] The lubricant is one or more of octadecanoic acid, modified polyester wax, polyethylene wax, modified polyethylene wax, erucamide, oleamide, and stearic acid.

[0026] In a second aspect, the present application provides a method for preparing a UV-crosslinked highly transparent polyvinyl chloride cable material, using the following technical solution: A method for preparing a UV-crosslinked highly transparent polyvinyl chloride cable material comprises the following steps: S1, mixing the modified catalyst, the photoinitiator and the cross-linking agent, crushing and sieving to obtain a mixture; S2, blending the mixture, polyvinyl chloride resin, plasticizer, lubricant, antioxidant and stabilizer, extruding and granulating to obtain.

[0027] By adopting the above technical solution: fewer process steps, it is conducive to the industrial scale-up of cable material preparation, and can be cross-linked by ultraviolet light, which facilitates the one-stop production of extrusion, cross-linking, slitting and other steps in the production process, which is simple and efficient; and the mechanical properties, thermal properties and electrical properties of the prepared cable material are better.

[0028] In summary, this application has the following beneficial effects: 1. Adding modified catalysts, relying on the interaction between the rare earth ions contained in them and different functional groups, improves the heat resistance of polyvinyl chloride, inhibits the chain reaction of macromolecular chain dehydrogenation, and promotes the rapid cross-linking of cable materials under ultraviolet light; introducing EVA resin not only improves the transparency of cable materials, thereby facilitating rapid cross-linking, but also reduces the loss and deactivation of rare earth catalysts through coating, thus preparing a cable material with light curing, rapid cross-linking, and good mechanical, thermal and electrical properties; 2. It is preferred to use EVA resin with a vinyl acetate content of ≥30%, which has many functional groups and high polarity, which is conducive to the cross-linking reaction; it also has good fluidity, is conducive to dispersion, has a better coating effect on rare earth catalysts, and effectively protects the activity of rare earth; 3. The preparation process is carried out in steps. The modified catalyst, photoinitiator and cross-linking agent are pre-blended and refined to facilitate the subsequent full dispersion of the three in polyvinyl chloride, thereby improving the transparency, mechanical, electrical and thermal properties of the cable material. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Among them: EVA with a vinyl acetate content of 30% is from DuPont, USA, model 3185; EVA with a vinyl acetate content of 35% is from Mitsui Polymer, Japan, model P3307; polyester plasticizer is from Shandong Changyao New Materials Co., Ltd., model CY-D2; epoxidized soybean oil is from Jinan Hongchuang Chemicals Co., Ltd., model 1241; polyethylene wax is from Dongguan Zhengtao Plastic Co., Ltd., model PE wax; modified polyester wax is from Wengkaier (Guangdong) Technology Co., Ltd., model Cerelene 691; oxidized polyethylene wax is from Hefei Qihong Polymer Materials Co., Ltd., model OA10; modified polyethylene wax is from Shanghai Zhenlishi Network Technology Co., Ltd., model LANCO TF1788.

[0031] Preparation Example 1 A modified catalyst is obtained by using EVA solution as a wall material and coating a rare earth catalyst; the modified catalyst is prepared specifically by the following steps: Add 10 kg of EVA resin to 10 kg of ethylene glycol ethyl ether acetate, stir and mix at 25 ° C for 5 hours to obtain an EVA solution; add 2 kg of cerium oxide to the EVA solution, stir and mix at 40 ° C for 20 hours, and dry at 70 ° C for 8 hours to obtain; Among them, the vinyl acetate content of EVA resin is 30%.

[0032] Preparation Example 2 A modified catalyst is prepared by the following steps: Add 7 kg of EVA resin to 10 kg of ethylene glycol ethyl ether acetate, stir and mix at 25° C. for 5 hours to obtain an EVA solution; add 1.2 kg of neodymium oxide to the EVA solution, stir and mix at 40° C. for 20 hours, and dry at 70° C. for 8 hours to obtain; Among them, the vinyl acetate content of EVA resin is 35%.

[0033] Preparation Example 3 A modified catalyst is prepared by the following steps: Add 5 kg of EVA resin to 10 kg of ethylene glycol ethyl ether acetate, stir and mix at 25° C. for 5 hours to obtain an EVA solution; add 1.5 kg of praseodymium oxide to the EVA solution, stir and mix at 40° C. for 20 hours, and dry at 70° C. for 8 hours to obtain; Among them, the vinyl acetate content of EVA resin is 30%.

[0034] Preparation Example 4 A modified catalyst is prepared by the following steps: Add 5 kg of EVA resin to 10 kg of ethylene glycol ethyl ether acetate, stir and mix at 25 ° C for 5 hours to obtain an EVA solution; add 1.3 kg of samarium oxide to the EVA solution, stir and mix at 40 ° C for 20 hours, and dry at 70 ° C for 8 hours to obtain; Among them, the vinyl acetate content of EVA resin is 30%.

[0035] Preparation Example 5 A modified catalyst is prepared by the following steps: Add 10 kg of EVA to 10 kg of ethylene glycol ethyl ether acetate, stir and mix at 25° C. for 5 hours to obtain an EVA solution; add 1.5 kg of cerium oxide and 0.5 kg of lanthanum oxide to the EVA solution, stir and mix at 40° C. for 20 hours, and dry at 70° C. for 8 hours to obtain; Among them, the vinyl acetate content of EVA resin is 30%.

[0036] Example 1 A UV-crosslinked highly transparent polyvinyl chloride cable material is prepared by the following steps: S1, 12 kg of modified catalyst (prepared in Preparation Example 1), 1.3 kg of photoinitiator MMMP, and 2.0 kg of crosslinking agent TAIC were mixed, ground, and passed through a 20-mesh sieve to obtain a mixture; S2. The mixture, 100 kg of polyvinyl chloride resin, a plasticizer (15 kg of polyester plasticizer, 3.0 kg of DOS, 7 kg of epoxidized soybean oil), 1.2 kg of a lubricant (polyethylene wax), 0.2 kg of an antioxidant HP136, and 1.6 kg of a stabilizer (di-n-octyltin maleate) are blended, added into a twin-screw extruder (aspect ratio 28:1), extruded (screw speed 30 rpm, heating zone 1 temperature 120° C., heating zone 2 temperature 130° C., heating zone 3 temperature 150° C., heating zone 4 temperature 140° C.), and granulated to obtain a cable material.

[0037] Among them, the degree of polymerization of polyvinyl chloride resin is 1000, it is sourced from Formosa Plastics Corporation in Taiwan, and its model is S-65.

[0038] Example 2 A UV-crosslinked highly transparent polyvinyl chloride cable material is prepared by the following steps: S1, 8.2 kg of modified catalyst (prepared in Preparation Example 2), 1.6 kg of photoinitiator 907, and 1.8 kg of crosslinking agent TMCH were mixed, ground, and passed through a 20-mesh sieve to obtain a mixture; S2. Blend the mixture, 100 kg polyvinyl chloride resin, plasticizer (15 kg TOTM, 3.0 kg DOA, 8 kg epoxidized soybean oil), 1.5 kg stabilizer (dibutyltin dilaurate), 0.3 kg antioxidant 1520, and 1.0 kg lubricant (modified polyester wax), add them into a twin-screw extruder (length-to-diameter ratio 28:1), extrude (screw speed 35 rpm, heating zone 1 temperature 120°C, heating zone 2 temperature 130°C, heating zone 3 temperature 150°C, heating zone 4 temperature 140°C), and granulate to obtain the cable material.

[0039] Among them, the degree of polymerization of polyvinyl chloride resin is 1300, it is sourced from Taiwan Formosa Plastics, and its model is S-70.

[0040] Example 3 A UV-crosslinked highly transparent polyvinyl chloride cable material is prepared by the following steps: S1, 6.5 kg of modified catalyst (prepared in Preparation Example 3), 2.0 kg of photoinitiator DEAP, and 1.4 kg of cross-linking agent DHBP were mixed, ground, and passed through a 20-mesh sieve to obtain a mixture; S2. Blend the mixture, 100 kg polyvinyl chloride resin, plasticizer (15 kg TOTM, 3.0 kg DOS, 7 kg epoxidized soybean oil), 1.0 kg lubricant (oxidized polyethylene wax), antioxidant (0.1 kg HP136, 0.2 kg 1520), and 1.5 kg stabilizer BT-53C, add into a twin-screw extruder (length-to-diameter ratio 28:1), extrude (screw speed 35 rpm, heating zone 1 temperature 120°C, heating zone 2 temperature 130°C, heating zone 3 temperature 147°C, heating zone 4 temperature 140°C), and granulate to obtain the cable material.

[0041] Among them, the degree of polymerization of polyvinyl chloride resin is 1800, it is sourced from Taiwan Formosa Plastics, and its model is S-80.

[0042] Example 4 A UV-crosslinked highly transparent polyvinyl chloride cable material is prepared by the following steps: S1, 6.3 kg of modified catalyst (prepared in Preparation Example 4), 1.5 kg of cross-linking agent DTBP, and 2.0 kg of photoinitiator 369 were mixed, ground, and passed through a 20-mesh sieve to obtain a mixture; S2. The mixture, 100 kg of polyvinyl chloride resin, plasticizer (20 kg of polyester plasticizer, 3.0 kg of DOA, 8 kg of epoxidized soybean oil), 1.5 kg of stabilizer TVS 8831, antioxidant (0.1 kg of BHT, 0.2 kg of 1520), and 1.0 kg of lubricant (oxidized polyethylene wax) are blended, added into a twin-screw extruder (length-to-diameter ratio 28:1), extruded (screw speed 35 rpm, heating zone 1 temperature 115° C., heating zone 2 temperature 130° C., heating zone 3 temperature 145° C., heating zone 4 temperature 140° C.), and granulated to obtain the cable material.

[0043] Among them, the degree of polymerization of polyvinyl chloride resin is 2500, it is sourced from Taiwan Formosa Plastics, and its model is S-85.

[0044] Example 5 A UV-crosslinked highly transparent polyvinyl chloride cable material is prepared by the following steps: S1, 12 kg of modified catalyst (prepared in Preparation Example 5), 2.0 kg of cross-linking agent DTA, and 1.3 kg of photoinitiator MMMP were mixed, ground, and passed through a 20-mesh sieve to obtain a mixture; S2. The mixture, 100 kg of polyvinyl chloride resin, plasticizer (15 kg of TOTM, 3.0 kg of DOS, 8 kg of epoxy soybean oil), 1.6 kg of stabilizer (dibutyltin thioglycolate), antioxidant (0.2 kg of HP136, 0.1 kg of 120), and 1.2 kg of lubricant (modified polyethylene wax) are blended, added into a twin-screw extruder (length-to-diameter ratio 28:1), extruded (screw speed 35 rpm, heating zone 1 temperature 120°C, heating zone 2 temperature 130°C, heating zone 3 temperature 145°C, heating zone 4 temperature 140°C), and granulated to obtain the cable material.

[0045] Among them, the degree of polymerization of polyvinyl chloride resin is 1000, it is sourced from Formosa Plastics Corporation in Taiwan, and its model is S-65.

[0046] Comparative Example 1 A cable material, which is different from Example 1 in that no modification catalyst is added.

[0047] Comparative Example 2 A cable material, which is different from Example 1 in that cerium oxide is used instead of the modified catalyst.

[0048] Comparative Example 3 A cable material, which is different from Example 1 in that the amount of the modified catalyst used is 5 kg.

[0049] Example 4 A cable material, which is different from Example 1 in that the amount of the modified catalyst used is 15 kg.

[0050] Performance Testing For the cable materials prepared in the embodiments and comparative examples, the power was 5W / cm 2 The samples were irradiated for 5 s and 10 s, and then tested according to the HⅡ-90 standard in GB / T 8815-2008. The results were recorded in the following table.

[0051] Among them, the thermal extension test conditions are 200℃, 15min; the thermal aging tensile strength test conditions are 135℃, 240h; and the thermal aging mass loss test conditions are 115℃, 240h.

[0052] Table performance test results Referring to the above table, in Examples 1-5, due to the use of the modified catalyst prepared in the preparation example, the prepared cable materials have excellent mechanical properties and meet the use requirements of the cable materials; and compared with Comparative Example 1 in which no modified catalyst is added and Comparative Example 2 in which an equal amount of rare earth catalyst is added, after the modified catalyst is added, the heat deformation temperature, 200°C thermal stability time, air thermal aging and other heat resistance properties of the cable material, as well as electrical properties such as dielectric constant are significantly improved.

[0053] In contrast, since no modified catalyst was added to Comparative Example 1-2, the cable material produced had basically no thermal elongation and the gel content could not be measured, indicating that adding rare earth catalysts through the sol-gel method can significantly improve the various properties of the cable material.

[0054] The difference between Comparative Examples 3-4 and Example 1 is that the amount of modified catalyst used is different. The various properties of the prepared cable material are all reduced, indicating that when the amount of modified catalyst used is within the range of the examples of the present application, the various properties of the cable material can be significantly improved.

[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A UV-crosslinked highly transparent polyvinyl chloride cable material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of polyvinyl chloride resin, 25-31 parts of plasticizer, 1.4-2.0 parts of crosslinking agent, 1.3-2.0 parts of photoinitiator, 1.5-1.6 parts of stabilizer, 0.2-0.3 parts of antioxidant, 1.0-1.2 parts of lubricant and 6.3-12 parts of modified catalyst; The modified catalyst is obtained by using EVA solution as the wall material and coating the rare earth catalyst.

2. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 1, characterized in that: The EVA solution is a mixed solution of EVA resin and ethylene glycol ethyl ether acetate, and the vinyl acetate content of the EVA is ≥30%.

3. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 2, characterized in that: The weight ratio of the EVA resin to ethylene glycol ethyl ether acetate is (0.5-1):

1.

4. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 3, characterized in that: The weight ratio of the rare earth catalyst to the EVA resin is 1:(5-10).

5. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 4, characterized in that: The rare earth catalyst is one or more of neodymium chloride, neodymium oxide, praseodymium oxide, lanthanum oxide, cerium oxide, and samarium oxide.

6. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 1, characterized in that: The polymerization degree of the polyvinyl chloride resin is 1000-2500.

7. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 1, characterized in that: The plasticizer is one or more of dibutyl phthalate, dioctyl phthalate, trioctyl trimellitate, dioctyl terephthalate, diisononyl cyclohexane-1,2-dicarboxylate, polyester plasticizer, epoxy soybean oil, dioctyl sebacate, and dioctyl adipate.

8. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 1, characterized in that: The crosslinking agent is one or more of 1,1-bis(tert-butylperoxide)-3,3,5-trimethylcyclohexane, trithiocyanuric acid, triallyl isocyanurate, zinc acetylacetonate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide, diethylenetriamine, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-isopropylimidazole, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, triethylenetetramine, dimethylaminopropylamine, and vinyltriethoxysilane.

9. The ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to claim 1, characterized in that: The photoinitiator is: phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-methyl-1- (4-methylthiophenyl) -2-morpholinyl-1-propanone, 2-dimethylamino-2- (4-methyl) benzyl-1- [4- (4-morpholinyl) phenyl] -1-butanone, benzoin dimethyl ether, benzoin ethyl ether, benzoin butyl ether, diphenyl acetophenone, α, α-dimethoxy-α-phenyl acetophenone, α, One or more of α-diethoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone, bisbenzoylphenylphosphine oxide, benzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

10. A method for preparing the ultraviolet light cross-linked high-transparency polyvinyl chloride cable material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the modified catalyst, the photoinitiator and the cross-linking agent, crushing and sieving to obtain a mixture; S2, blending the mixture, polyvinyl chloride resin, plasticizer, lubricant, antioxidant and stabilizer, extruding and granulating to obtain.